Unique Police Training Polygon in Terms of Activity and Training Improvement of the Intervention Units of the Police of the Czech Republic - Hrinko, Martin (Communications - Scientific letters of the University of Zilina, 2017)
The report describes project works and the purpose of a special training polygon designated for police officers of intervention units of the Police of the Czech Republic. It is a completely unique training facility newly built for the law enforcement officers. It concerns the outstanding project in conditions of the Police of the Czech Republic, which contains extreme situations and conditions which police officers of intervention and special units can meet in their practical performance of service. In the limited extend this applies also for the training of tactics for members of firstly coming patrols and emergency units.